MAY-THURNER SYNDROME: WHAT RADIOLOGISTS NEED TO EVALUATE ON COMPUTED TOMOGRAPHY IMAGING? - Thị Thanh Tâm, Bùi; Võ Công Nguyên, Đỗ; Thanh Phong, Trần; Nguyên Thuận, Huỳnh (Journal of Health and Aging, 2025)
May-Thurner syndrome is a vascular compression syndrome in which the left common iliac vein is compressed between the lower lumbar spine and the right common iliac artery. This condition can cause lower extremity venous thrombosis, and profound venous thrombosis, leading to life-threatening complications. The treatment of May–Thurner syndrome differs from other causes of non-compressive lower extremity thrombosis. Therefore, radiologists must recognize this condition to help patients receive accurate and timely treatment. Among diagnostic imaging methods, computed tomography is the superior imaging method, providing useful information for the treatment of May–Thurner syndrome. This essay aims to assist radiologists in maximizing the advantages of MDCT, from protocol to image interpretation, in a comprehensive examination of a patient with suspected May-Thurner syndrome.
Keywords: May-Thurner syndrome; deep venous thrombosis; Computed tomography